Jamaica : Thirteenth Review under the Arrangement Under the Extended Fund Facility-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Jamaica's Thirteenth Review Under the Arrangement Under the Extended Fund Facility. Program implementation is on track. The authorities' continued commitment to the demanding reform program even in the fourth year of the IMF-supported program is commendable. All quantitative performance criteria to be completed by the end of June 2016, as well as the continuous quantitative program targets and structural benchmarks, have been met. Domestic confidence indicators are at an all-time high, and there are signs of improving economic activity, including agricultural recovery, strong performance in tourism and manufacturing, and stronger private sector credit growth. Higher growth dividends, more job creation, and improved living standards will be essential to continued social support for the reform agenda.